2023
DOI: 10.21203/rs.3.rs-2649903/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of the intestinal microbes associated with muscle strength

Abstract: Background Considering the effect of the gut microbiome on human physiology and aging, the gut microbiome may affect muscle strength in the same way as the host's own genes. Previous research has shown that the gut microbiome can have both positive and negative effects on muscle strength, suggesting the presence of two different types of gut microbiome. In this study, we demonstrate that the gut microbiome can contribute differently to muscle strength. Results We remodelled the original gut microbiome of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Fold-change comparison showed that Eisenbergiella massiliensis and Anaeroplasma abactoclasticum from the gut microbiome had positive contributions to muscle strength, while Ileibacterium valens and Ethanoligenens harbinense had negative effects. Therefore, this study successfully demonstrated that in vivo subset analysis of the human gut microbiome using animal models is a useful approach for studying complex and heterogeneous populations comprised of trillions of microorganisms, and we believe that this concept can be applied to identify gut microbiome associated with other human phenotypes or diseases [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fold-change comparison showed that Eisenbergiella massiliensis and Anaeroplasma abactoclasticum from the gut microbiome had positive contributions to muscle strength, while Ileibacterium valens and Ethanoligenens harbinense had negative effects. Therefore, this study successfully demonstrated that in vivo subset analysis of the human gut microbiome using animal models is a useful approach for studying complex and heterogeneous populations comprised of trillions of microorganisms, and we believe that this concept can be applied to identify gut microbiome associated with other human phenotypes or diseases [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…(Alpha Biochemicals Co, Jeonju, Republic of Korea)) to create a composite fecal mixture containing a variety of human gut microbes. The human fecal mixture was orally administered to the mice at a volume of 20 µL, using the gavage method 39 , twice a day for 2 days. Prior to the administration of the human fecal mixture and three months after, all mice were weighed, and feces and blood samples were individually collected.…”
Section: Study Design and Animal Experimentsmentioning
confidence: 99%
“…The serum levels of TCHO, TG, and HDL-C and blood glucose level were determined using commercial assay kits (Asan Pharmaceutical, Seoul, South Korea) following the manufacturer's instructions, as previously described. 41,42 DNA extraction and 16S rRNA gene sequencing…”
Section: Analyses Of Biochemical Parametersmentioning
confidence: 99%
“…The medium was then autoclaved for 22 min at 121 • C, cooled to below 40 • C, and supplemented with 2 mL of filter sterilized (0.22 µm) vitamin solution (prepared through mixing 0.02 g of biotin, 0.02 g of cyanocobalamin, 0.03 g of P-amino benzoic acid, 0.05 g of folic acid, 0.15 g of pyridoxine HCl, 0.05 g of thiamine HCl, 0.05 g of riboflavin, 0.05 of L-ascorbic acid, 0.02 g of coenzyme q 10, 0.2 g of L-glutamine, 0.03 g of dimethylglycine, 0.03 g of inositol, 0.03 g of niacin, 0.03 g of L-carnitine, 0.03 g of methylsulfonylmethane, and 100 µL of vitamin K1 in 1 L of dd H 2 O) and 50 mL of pig blood. The medium was deoxygenated and stored in an anaerobic container before use [53].…”
Section: Study Design and Animal Experimentsmentioning
confidence: 99%